1990
DOI: 10.1182/blood.v75.1.88.88
|View full text |Cite
|
Sign up to set email alerts
|

Binding of G-CSF, GM-CSF, tumor necrosis factor-alpha, and gamma- interferon to cell surface receptors on human myeloid leukemia cells triggers rapid tyrosine and serine phosphorylation of a 75-Kd protein

Abstract: Granulocyte colony-stimulating factor (G-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), gamma-interferon (gamma-IFN), or tumor necrosis factor-alpha (TNF-alpha) triggered the rapid, stable phosphorylation of a 75-Kd protein (p75) when incubated with permeabilized HL60 human myeloid leukemia cells in the presence of [gamma-32P] ATP. Among several chemical inducers of HL60 cell differentiation, dimethyl sulfoxide also triggered p75 labeling, but retinoic acid or 12-O-tetradecanoylphorbol-13-ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…It is likely that this region is involved in activation of common or highly related signal transduction pathways. This notion is supported by several receptor transfection studies (7,15,29,35,48) and by the fact that some of the ligands for these receptors induce similar patterns of tyrosine phosphorylation (9,27,36).…”
Section: Discussionmentioning
confidence: 80%
“…It is likely that this region is involved in activation of common or highly related signal transduction pathways. This notion is supported by several receptor transfection studies (7,15,29,35,48) and by the fact that some of the ligands for these receptors induce similar patterns of tyrosine phosphorylation (9,27,36).…”
Section: Discussionmentioning
confidence: 80%
“…Although TNFa receptors do not themselves appear to have intrinsic kinase activity (Schall et al, 1990;Smith et al, 1990), several reports (Schutze et al, 1989;Kaur et al, 1989;Robaye et al, 1989;Evans et al, 1990) have described the TNFa-induced phosphorylation of distinct cytosolic proteins in different human of molecular masses 130, 90, 80, 65 and 42 kDa was found. Subsequently, we found a similar pattern of increased phosphorylation following stimulation of AlO cells with mezerein, a phorbol ester derivative which activates PKC, a serine/threonine kinase.…”
Section: Introductionmentioning
confidence: 99%
“…AA can be metabolized to leukotrienes and prostaglandins, potent mediators of inflammatory processes. In addition, protein kinases (PK) appear to play a crucial role in TNF signal transduction pathways (27)(28)(29)(30)(31), and a number of cellular substrates for TNF-responsive PK have been detected (32)(33)(34)(35)(36)(37)(38)(39). We have recently shown that TNF stimulates translocation and activation of PKC (30).…”
mentioning
confidence: 99%